2021
DOI: 10.3233/jad-210599
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Genetic Marker for the C9orf72 Repeat Expansion in the Finnish Population

Abstract: Background: C9orf72 repeat expansion (C9exp) is the most common genetic cause underlying frontotemporal lobar degeneration (FTLD) and amyotrophic lateral sclerosis (ALS). However, detection of the C9exp requires elaborative methods. Objective: Identification of C9exp carriers from genotyped cohorts could be facilitated by using single nucleotide polymorphisms (SNPs) as markers for the C9exp. Methods: We elucidated the potential of the previously described Finnish risk haplotype, defined by the SNP rs3849942, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…As recently demonstrated, the high rate found in Northern Savo may be linked to the prevalence of C9orf72 sequence variations specifically found in this area, as compared with other Finnish areas (ie, Northern Ostrobothnia). 30 Conversely, the low incidence detected in the Netherlands and in Stockholm might be due to incomplete ascertainment and nonuniform assessments in place across registries, which could also influence bias toward specific phenotypes. This interpretation needs to be confirmed in future prospective studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As recently demonstrated, the high rate found in Northern Savo may be linked to the prevalence of C9orf72 sequence variations specifically found in this area, as compared with other Finnish areas (ie, Northern Ostrobothnia). 30 Conversely, the low incidence detected in the Netherlands and in Stockholm might be due to incomplete ascertainment and nonuniform assessments in place across registries, which could also influence bias toward specific phenotypes. This interpretation needs to be confirmed in future prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, from a geographical point of view, estimated FTLD incidence captured a relative homogeneity among different countries, with the exception of 1 district surveyed in Finland (Northern Savo) with the highest incidence rate and comparatively low incidence rates found in the Netherlands and Sweden. As recently demonstrated, the high rate found in Northern Savo may be linked to the prevalence of C9orf72 sequence variations specifically found in this area, as compared with other Finnish areas (ie, Northern Ostrobothnia) . Conversely, the low incidence detected in the Netherlands and in Stockholm might be due to incomplete ascertainment and nonuniform assessments in place across registries, which could also influence bias toward specific phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The HRE-containing haplotypes seem to differ among European populations. It was previously shown that rs139185008 was not among the top SNPs associated with ALS in the UK Biobank (Rostalski et al, 2021). Here, we tested SNPs identified as HREtagging SNPs in a cohort from the Netherlands and United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…Rs139185008 has been previously reported as the top HRE tagging SNP in Finland and associated with idiopathic normal pressure hydrocephalus as well as with FTD (3 × 10 −15 , OR 4.38) and ALS (3 × 10 −21 , OR 5.19) in the FinnGen release 5 (Korhonen et al, 2019;Rostalski et al, 2021).…”
Section: Als Case-control Cohort: C9orf72 Hexanucleotide Repeat Allel...mentioning
confidence: 99%
“…This risk may be conferred by the IAs as such, other variation on the haplotype or their combination. Haplotype heterogeneity regarding the best expansion-tagging SNPs has already been reported between Finnish and UK populations [ 10 ] and the above-mentioned differences in the frequencies of the 17–19 and ≥ 20 repeat alleles may reflect differences in the haplotype background of these alleles.…”
mentioning
confidence: 99%